Statistical survey design and evaluating impact - Roy, Tarun Kumar; Acharya, Rajib; Roy, Arun Kumar (Delhi: Cambridge University Press, 2016)
""Discusses the methodologies to design sample surveys and evaluation techniques that are useful for large scale surveys"--Provided by publisher"--
Includes bibliographical references and index.
Keywords: Surveys -- Methodology; Sampling (Statistics)